Joro's Youth: The first part of the Mongolian epic of Geser Khan - de Rachewiltz, Igor (ANU Press, 2017)
The epic of King Gesar of Ling is the national oral epic of Tibet, sung by itinerant bards in their land for many centuries but not recorded in print until recent times. Spreading widely beyond Tibet, there are extant versions in other languages of Central Asia. The first printed version is from Mongolia, produced on the orders of the Kangxi emperor of the Manchu Qing dynasty in the early 18th century. In the process of transmission, the original saga lost much of its Tibetan flavour, and this Qing edition can be regarded as a genuine Mongolian work. Its hero, Geser Khan in Mongolian, became a folk-hero, later deified both in China and Mongolia. Geser's mission is to save the world from endemic evil and strife, bringing peace to all. Although he himself is the son of a god, Geser as a human is unpredictable, romantic and funny, and many of his adventures belong to the picaresque. This translation of the first, and one of the longest, chapters of the epic covers his miraculous birth, his turbulent youth, and his marriage to the beautiful Rogmo Goa. It celebrates and commemorates the 300th anniversary of the printing of the epic in Peking in early 1716.